PREDICTORS OF INCEST SURVIVORS’ IN THE EMOTIONAL AND BEHAVIORAL COMPETENCIES - Joson , Kathreen C.; Luna, Gabriel L. (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to find out the predictors of incest survivors’ emotional and behavioral competencies. Employing the descriptive-correlational design and case study method, the research involved the fifteen incest survivors who stayed at the Women and Children Protection Center for temporary custody. It also utilized the standardized psychological examinations, the Problem Behavior Inventory and the Social Emotional Assets Scales, which were translated in Filipino for better understanding. Data were analyzed using the frequency and percentage, arithmetic mean, Pearson r, and stepwise multiple regression. In view of the findings of the research, the study concludes that majority of incest survivors are 6 to 15 years old, eldest and middle child, living with their father, parents and relatives, with parents’ marital status as living together and separated. Majority of respondents’ fathers are engaged in tricycle driving and farming; their mothers as vendor, laundry woman, housewife and Overseas Filipino Workers. Most incest survivors’ families belong to the Food Threshold Level with monthly earning of 6,125.00 and work location in the rural areas. Most of them are with ages 6-15 onset of sexual abuse perpetrated by their biological fathers; who have on-going status of litigation. The most common psychological distresses of incest survivors were somatic disorder, mood disorder, anxiety disorder, sleep disorder, and parent-child problem. The level of respondents’ emotional and behavioral competencies is average to high functioning, while the level of empathy, self-competence and total emotional and behavioral competencies is at risk. Those incest survivors with fathers who worked as tricycle drivers and farmers and mothers serving as housekeepers, laundry women and vendor with parents ‘place of occupation located in rural areas tended to perform higher in their emotional and behavioral competencies. The more the incest survivors experience eating disorder and academic problem as psychological distresses, they tend to have lower level of self-regulation in the emotional and behavioral competencies; the greater is the respondents’ mood disorder, the lesser is the level of social competence and responsibility; and the greater is the conduct disorder, the lower is the incest survivors’ total emotional and behavioral competencies. Father’s occupation, academic problem and conduct disorder as psychological distresses of the incest survivors explain self- regulation; young incest survivors with parents living together and the occurrence of more psychological distresses explain the incest survivors’ social competence; fathers’ low income with blue collar job and conduct disorder explain the incest survivors’ responsibility; while the incest survivors’ age determined empathy; and finally, mood disorder of respondents explains their emotional and behavioral competencies.